Ahmad Hassan and Islamic Legal Reform in Indonesia ( 1887 - 1958 ) - MINHAJI, Akhmad (Kurnia Kalam Semesta Press, 2001)
There is a perception, held not only by scholars in the field but by many Muslims as well, that Islamic law in Indonesia is strongly colored by "non-Islamic" local custom (adat). Historically, this notion has given rise to a number of movements which have sought to ensure that religious beliefs and practices be restored and brought into harmony with the primary sources of Islam, the Qur'an and Sunnah. One of these movements was led by Ahmad Hassan (1887-1958), acknowledged by many as a great scholar and a tireless advocate of the need for renewal (tajdid) and reform (islah). This study analyses the significance of Hassan's role in the movement for Islamic legal reform and examines in particular his legal theory (usul al-fiqh) and its application to problems of substantive law (fiqh). In terms of Indonesia (and perhaps other regions as well), this is a new approach; for few works on Islamic law in Indonesia concerned with either the Islamic judicial system or substantive law devote any significant attention to usul al-fiqh, which, in fact, provides the foundation for these institutions, not to mention other aspects of Islamic teaching as well. As a reformer, Hassan was sometimes led to adopt bold, even extreme positions. He attacked his traditionalist opponents for placing too much faith in the doctrines of particular legal schools when seeking solutions to the problems faced by Muslims. Too often this led them to base their decisions on individual opinion, which placed them at a doble remove from the two primary sources. Instead Hassan advocated constant ijtihad, or at least ittiba', in the belief that the door had never been shut on direct analysis of scripture. In adopting this position, Hassan developed a sound, consistent and text-based approach to usul al-fiqh that was adopted after his death by his followers and students. Indeed, this approach has even had a substantial effect on his opponents, whose stance has changed subtly to reflect many of Hassan's concerns.